857. A Tele-Antibiotic Stewardship Program Influences Antibiotic Use at 2 Rural Veterans Affairs Medical Centers. (26th November 2018) - Wilson, Brigid; Banks, Richard; Crnich, Christopher; Ide, Emma; Viau, Roberto; El Chakhtoura, Nadim G; Jones, Yvonne; Cherry, Jason; Anderson, Brett; Urban, Andrew; Jump, Robin
Abstract: Background: Telehealth offers the possibility of supporting antibiotic stewardship in settings with limited access to people with infectious diseases (ID) expertise. Previously, we described preliminary results from a pilot project that used the Veterans Affairs (VA) telehealth system to facilitate a Videoconference Antimicrobial Stewardship Team (VAST) which connected a multidisciplinary team from a rural VA medical center (VAMC) with ID physicians at a remote site to support antibiotic stewardship. Here, we present 3 distinct metrics to assess the influence of the VAST on antibiotic use at 2 intervention sites. Methods: Outcomes assessed antibiotic use in the hospital and long-term care units of 2 rural VAMCs in the year before and after VAST implementation, allowing for a 1-month wash-in period in the first month of the VAST. Using VA databases, we determined 3 metrics: the rate of antibiotic use (days of therapy per 1, 000 bed days of care); the mean length of therapy (days); and the mean patient antibiotic spectrum index (ASI), a measure of antibiotic spectrum increasing from narrow to broad. Using segmented regression on monthly measures of each metric with a knot at the wash-in month (gray square), we calculated predicted values (solid lines), and confidence intervals (dashed lines) to examine trends before (black squares) and after (white squares) implementing the VAST. Results: The rate of antibiotic use, mean length of therapy, and ASI decreased at Site A. As indicated in the figure, the effect was more pronounced in long-term care compared with the hospital, where the VAST sustained but did not accelerate downward trends. At Site B, the most notable influence of the VAST was on the ASI for the hospital and long-term care units. Conclusion: The VAST is a feasible, sustainable program that is effective at inducing change in antibiotic use at 2 VAMCs. The influence of the VAST differed between the 2 sites and, at Site A had a more pronounced effect on the long-term care compared with hospital units. These distinct metrics capture changes in overall antibiotic use, length of therapy, and agent selection. Tele-antibiotic stewardship programs hold potential to improve antibiotic use at facilities with limited access to people with antibiotic stewardship expertise. Disclosures: All authors: No reported disclosures.